Pengetahuan, Sikap, Zat Pengawet, Pewarna Berbahaya Terhadap Tindakan Siswa dalam Pemilihan Jajanan di SMP - Chatrine Virginia Tamara; Febriantika Febriantika (Syntax Corporation Indonesia, 2023)
Snacks for school children are very diverse, can be in the form of food and drinks. The habit of parents not providing provisions and giving pocket money to their children has been going on for a long time. Even though the school has a school canteen, many school children eat snacks carelessly and buy food and drink snacks from food vendors selling their wares around the school. Until now, the safety level of snacks for school children is apprehensive. Misuse of hazardous chemicals such as formalin, borax, rhodamine B, and methanil yellow. This study aims to determine the relationship between knowledge and attitudes about harmful preservatives and dyes towards the actions of class VIII students in choosing snacks at Tanjung Morawa Methodist Middle School, 2016. This type of research was observational with a cross-sectional design and a sample technique used in the study with a total a sample of 51 students were selected by means of systematic sampling. Data was collected through interviews using a questionnaire. Data analysis used included univariate analysis and bivariate analysis using the Chi Square test. The results of this study indicate that there is a relationship between knowledge about harmful preservatives and dyes towards the actions of class VIII students in choosing snacks at Tanjung Morawa Methodist Middle School, 2016 with a p value of 0.024 and there is an attitude about harmful preservatives and dyes towards the actions of class VIII students in choosing food. snacks at Tanjung Morawa Methodist Middle School, 2016 with a p value of 0.002.